Pengelolaan Limbah Tekstil Pada Usaha Perdagangan Kain:Studi Kasus Toko Kain Zainul Dalam PerspektifHukum Lingkungan Hidup Di Indonesia - Muhamad Septrian Ramadhani; Nur Qoilun (CV. ITTC INDONESIA, 2026)
The textile trading sector is a significant component in the national fashion and convection industry chain. Beyond its contributions to the local economy, fabric trading activities also generate solid waste in the form of fabric scraps, plastic packaging, and other textile residues that can pollute the environment if not managed systematically. This study examines textile waste management practices at Toko Kain Zainul, a fabric trading business established in 2019 that now operates two branches with approximately 27 types of textile fabrics. A qualitative descriptive method with a case study approach was used, supplemented by a juridical review of applicable environmental law frameworks. The findings indicate that Toko Kain Zainul partially applies the 3R principles (reduce, reuse, recycle), where fabric scraps are reutilized through redistribution to local artisans, while plastic packaging waste is sorted before disposal. The legal review reveals that the waste management practices align with the spirit of Law No. 32 of 2009 on Environmental Protection and Management, although implementation remains informal and has not been systematized within a standardized environmental management framework. This article emphasizes the need for integration between textile trading business practices and sustainable environmental responsibility.